Multi-scenario dynamic analysis of demand for critical minerals in China’s new energy vehicles under “dual carbon” goals - Linchang, ZHENG; Wenqi, BAO; Ge, CHEN; Aomiao, GENG (Zi yuan ke xue, 2025)
[Objective] The implementation of the “dual carbon” goals in the transportation sector significantly affects the scale and performance of new energy vehicles, thereby altering the consumption demand for critical minerals in these vehicles. To actively address the supply and demand pressure on critical minerals, it is imperative to evaluate the impact of the “dual carbon” goals on the consumption demand of critical minerals for new energy vehicles in China. [Methods] Based on the Gompertz model, this study predicted the sales of new energy vehicles, and calculated and set the related parameters for new energy vehicles. The consumption demand for critical minerals in new energy vehicles from 2022 to 2035 was estimated under different “dual carbon” policy scenarios and lithium battery technology pathways. [Results] (1) The per-vehicle consumption of critical minerals varied across different types of new energy vehicles, with lithium consumption increasing in passenger battery electric vehicles and special-purpose battery electric vehicles. (2) The consumption demand for lithium, nickel, cobalt, neodymium, dysprosium, and praseodymium in new energy vehicles was expected to increase rapidly. Under the benchmark policy scenario, the annual growth rates of consumption demand were 15.97%~16.10%, 13.15%~17.01%, 7.42%~12.66%, 12.05%~14.24%, 11.94%~14.12%, and 11.94%~14.12%, respectively. (3) The production of new vehicles was the main contributor to the consumption demand for critical minerals in new energy vehicles, although its contribution was expected to decline. Passenger battery electric vehicles remained the primary contributor to consumption demand for critical minerals in new energy vehicles. Meanwhile, the contribution from battery swapping was projected to increase. (4) When adopting the same ternary battery technology pathways, new energy vehicles under aggressive policy scenarios demonstrated increased demand for lithium, nickel, cobalt, neodymium, dysprosium, and praseodymium. Under identical “dual carbon” policy scenarios, new energy vehicles adopting high-nickel and nickel-cobalt-aluminum battery technologies had higher demand for nickel, while those using low-nickel alternatives had higher demand for cobalt. [Conclusion] From 2022 to 2035, the rapid expansion of China’s new energy vehicle market, along with changes in per-vehicle mineral consumption, will significantly increase demand for critical minerals while exacerbating supply-demand tensions, particularly for lithium, cobalt, and nickel. To mitigate these pressures, it is necessary to promote green consumption of new energy vehicles, advance the development of a circular economy, optimize the global layout of industrial and supply chains, and strengthen technological research and development.